COMMUNITY LEVEL OF KNOWLEDGE ON THE RISK FACTORS OF TOXOPLASMOSIS IN SILIRAGUNG VILLAGE SILIRAGUNG DISTRICT BANYUWANGI REGENCY - Ahmad Anang Intan Purnama Negara; I MAde Sukada; Romy Muhammad Dary Mufa (Buletin Veteriner Udayana, 2024)
Toxoplasmosis is a zoonotic disease caused by the single-celled protozoa Toxoplasma gondii with other animals from the Filidae class (cat family) as definitive hosts. The purpose of this study was to determine the level of public understanding of the dangers of toxoplasmosis in Siliragung Village. The data collection method used a questionnaire by conducting interviews with the community consisting of pre-marital and post-marital women in Siliragung Village, Siliragung District, Banyuwangi Regency. The results of this study indicate that the level of knowledge of the people of Siliragung Village from pre-marital women obtains a score of 47%. This shows that the level of knowledge of pre-marital women in Siliragung Village regarding the risk factors for toxoplasmosis is quite adequate. Then, post-marital women get a score of 55%. This study concluded that pre-marital women in Siliragung Village, Siliragung District, Banyuwangi Regency had lower knowledge than post-marital women about the risk factors for toxoplasmosis.